The impact of pelvic floor surgery on female sexual function: a mixed quantitative and qualitative study. (10th September 2013) - Roos, AM; Thakar, R; Sultan, AH; de, JW; Paulus, ATG
<x xml:space="preserve">Abstract</x> Objective To assess whether the current condition‐specific sexual function questionnaire provides full insight into sexual function following pelvic floor surgery. Design Prospective, mixed quantitative and qualitative study. Setting Urogynaecology clinic in a large university hospital. Population Thirty‐seven women undergoing surgery for pelvic organ prolapse (POP) and/or stress urinary incontinence (SUI). Methods Women were seen before surgery and 3 months postoperatively. At both visits the Pelvic Organ Prolapse/Urinary Incontinence Sexual Function Questionnaire (PISQ) was completed and a qualitative face‐to‐face semi‐structured interview was conducted. PISQ total and domain scores, as well as the change in the preoperative and postoperative score, were calculated and analysed using Wilcoxon signed rank test and one‐sample t‐test. The qualitative data were systematically analysed using data‐matrices. Main outcome measures The impact of pelvic floor surgery on female sexual function. Results Significant improvement was seen for PISQ total score (P = 0.003) as well as Physical (P < 0.001) and Partner‐related (P = 0.002) domains, but not for the Behavioural/Emotive domain (P = 0.220). Analysis of qualitative data showed that improvement in sexual function was a result of cure of POP and SUI symptoms. Deterioration of sexual function was due to dyspareunia, fear of causing damage to the surgical result, new symptoms and a disappointing result of surgery. Conclusions Our qualitative data show that PISQ is limited in the assessment of sexual function after pelvic floor surgery as it does not assess most surgery‐specific negative effects on sexual function.